Penggunaan One Single System (OSS) Berbasis Cloud Computing dalam Layanan Akademik: Pendekatan Technology Acceptance Model (TAM) - Ningtyas, Mega Norman; Fikriah, Nur Laili; Su'ud, Fikriyatul Azizah (Universitas Islam Negeri Alauddin Makassar, 2023)
Digitalization is important for our life, and higher education is no exception. The process of submitting letters that are still manual needs to be changed to something practical and easy. That is a digital-based letter submission through a website. Therefore, our research aims to develop One Single System (OSS) based on Web Cloud Computing to improve the performance of management study program services with the Technology Acceptance Model (TAM) approach. This is done to support the accreditation process that is periodically carried out by the study program. This research uses quantitative methods with a descriptive approach. Our respondents are active students of the Management Study Program at UIN Maulana Malik Ibrahim Malang. For data analysis, we used structural equation model analysis to test the constructs we used (perceived security, perceived usefulness, perceived of use, intention to use actual usage). The results of our research show that the perceived security, effect of perceived usefulness, perceived ease of use on intention to use in ACCESS users and intention to use on acceptance of ACCESS. The existence of the system makes it safe, faster and easier to use, so that many students intend to use and accept the existence of our system, ACCESS.